(untitled) (XXI Century. Spanish Literature and Culture, 2016)
Throughout her career, the writer, Philologist and editor Gemma Pellicer (Barcelona, 1972) has contributed literary criticism to several magazines and newspapers, and also thought literature, aphorism, and brief narrative –short and micro-story, genres that apparently fit her like a glove. To date she has published two excellently produced anthologies which neatly cristallize her worldview, focused on artistic, existencial and metaphisical concerns: La danza de las horas (2012) and Maleza viva (2016), in which the still predominant micro-story co-exists with other hiper short forms such as the prose poem, the microdrama, the panorama, the aphorism, etc. In both books "the poetic and thoughtful alternates with the strictly narrative, displaying the great versatility of the micro-story", an "inbound genre", according to Merino, which is nourrished by different materials, and which asks for the author at their strongest skills as well as for a cultured and refined reader.